2015
DOI: 10.1007/s13197-015-2049-z
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular identification and characterization of lactic acid bacteria and yeasts isolated from Ethiopian naturally fermented buttermilk

Abstract: Lactic acid bacteria (LAB) and yeasts were enumerated and identified from naturally fermented buttermilk. Isolates were first subjected to chemical tests and then to molecular characterization. Molecular identification involved pure sequencing of 16s rRNA (LAB) and 18s rRNA (yeast) genes. Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (DGGE) was used for detection of microbiota composition. Eighty-five LAB and 26 yeast isolates obtained from 16 small-scale dairy farms were isolated and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The metabolism of carbohydrates by LAB is a similar observation to that made by Negussie et al 31 who observed that LAB isolated from Ethiopian naturally fermented buttermilk were able to utilise carbohydrates such as galactose, maltose, glucose, fructose, mannose and lactose. The results of the current study are supported by those of Ashmaig et al 32 who observed that LAB isolated from traditional Sudanese fermented camel's milk were able to ferment some carbohydrates.…”
Section: Carbohydrate Profile Of Labsupporting
confidence: 81%
“…The metabolism of carbohydrates by LAB is a similar observation to that made by Negussie et al 31 who observed that LAB isolated from Ethiopian naturally fermented buttermilk were able to utilise carbohydrates such as galactose, maltose, glucose, fructose, mannose and lactose. The results of the current study are supported by those of Ashmaig et al 32 who observed that LAB isolated from traditional Sudanese fermented camel's milk were able to ferment some carbohydrates.…”
Section: Carbohydrate Profile Of Labsupporting
confidence: 81%
“…Previously published reports have demonstrated the presence of LAB in buttermilk (Gebreselassie, Abay, & Beyene, 2016; Iranmanesh et al, 2012). LAB in buttermilk revealed new alternative for the treatment and prevention of the pathogenic bacteria capable of developing antibiotic resistance (Gutiérrez, Martínez‐Blanco, Rodríguez‐Aparicio, & Ferrero, 2016), which may suggest the diminution of pathogenic and resistant bacteria in buttermilk.…”
Section: Resultsmentioning
confidence: 91%
“…Buttermilk is a rich source of vitamins, proteins, and valuable fats. Its balanced nutritional composition also strengthens its nutraceutical and health-promoting claims [ 9 ]. Buttermilk has been described in two different types i.e., traditional and cultured, according to their method of preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Buttermilk is another very popular and desirable nutritional drink for lactose intolerant individuals, produced as a byproduct from the churning of the unfermented milk cream [ 8 ]. Buttermilk is also a rich source of proteins, vitamins, milk salts, and nutritional ingredients [ 9 ]. Currently, a wide range of buttermilk variants are available in the market but cannot be considered as health drinks due to added sugar, flavors, and preservatives in them, which can further impose serious health problems.…”
Section: Introductionmentioning
confidence: 99%